Non-Genomic AhR-Signaling Modulates the Immune Response in Endotoxin-Activated Macrophages After Activation by the Environmental Stressor BaP - Großkopf, Henning; Walter, Katharina; Karkossa, Isabel; von Bergen, Martin; Schubert, Kristin (Frontiers in Immunology, 2021)
Emerging studies revealed that the Aryl hydrocarbon receptor (AhR), a receptor sensing environmental contaminants, is executing an immunomodulatory function. However, it is an open question to which extent this is achieved by its role as a transcription factor or via non-genomic signaling. We utilized a multi-post-translational modification-omics approach to examine non-genomic AhR-signaling after activation with endogenous (FICZ) or exogenous (BaP) ligand in endotoxin-activated (LPS) monocyte-derived macrophages. While AhR activation affected abundances of few proteins, regulation of ubiquitination and phosphorylation were highly pronounced. Although the number and strength of effects depended on the applied AhR-ligand, both ligands increased ubiquitination of Rac1, which participates in PI3K/AKT-pathway-dependent macrophage activation, resulting in a pro-inflammatory phenotype. In contrast, co-treatment with BaP and LPS revealed a decreased AKT activity mediating an anti-inflammatory effect. Thus, our data show an immunomodulatory effect of AhR activation through a Rac1-ubiquitination dependent mechanism that attenuated AKT-signaling, resulting in a mitigated inflammatory response.